Regulation of the Escherichia coli K-12 uvrB operon. - Schendel, P F (1982)
The UV light inducibility of the uvrB operon of Escherichia coli K-12 was previously demonstrated by exploiting a strain in which the gene for the enzyme beta-galactosidase was inserted into the uvrB operon. This insert is now shown to be located within the structural gene for the uvrB enzyme, leaving the regulatory sequences of the operon intact. Analyses to quantitate the induction of this system show that derepression of the operon is first detectable 5 min after UV exposure, with the rate of synthesis increasing to four to six times the uninduced rate during the subsequent 30 min. Induction is unaffected by mutations in other components of nucleotide excision repair. The control of uvrB was found to result from direct repression by the lexA gene product, with the recA gene product playing an indirect role. Nucleotide excision repair thus seems to be part of the SOS response.